Impact of physical activity on the Body Mass Index and self-esteem of adolescents - Uchôa,Francisco Nataniel (2019)
The object of this study was to analyse the impact of the practice of physical activity on the body mass index (BMI) and self-esteem of adolescents. The samples included 1,011 adolescents, aged between 14 and 18 years. First the BMI was calculated, then the adolescents filled in the Rosenberg Self-esteem Scale (RSS) questionnaire and the International Physical Activity Questionnaire (IPAQ). Student's t-test and the chi-squared test were used for statistical analysis. The Odds Ratio and the Confidence Interval (95%) were also calculated. Female adolescents who are physically active have a 22.4% lower probability of developing overweight/obesity (OR=0.776, CI 95% 0.741-0.813) and 34.4% lower probability of presenting low self-esteem (OR=0.656, CI 95% 0.616-0.698). Participation in physical education classes reduces the probability that male adolescents will present low self-esteem by 88% (OR=0.120 CI 95% 0.043-0.339). In female adolescents, the practice of physical activity at school acts to prevent low self-esteem, as well as helping to control bodyweight increase. In male adolescents participation in physical education classes acts as a protection against low self-esteem.